Adalimumab Decorated Nanoparticles Enhance Antibody Stability and Therapeutic Outcome in Epithelial Colitis Targeting - Markus Ries; Brice Moulari; Maryam A. Shetab Boushehri; Mohamed Ehab Ali; Daniel Molnar; Arnaud Béduneau; Yann Pellequer; Alf Lamprecht (MDPI AG, 2022)
Inflammatory bowel disease (IBD) is a chronic inflammatory disease of the gastrointestinal tract with increasing incidence worldwide. Although a deeper understanding of the underlying mechanisms of IBD has led to new therapeutic approaches, treatment options are still limited. Severe adverse events in conventional drug therapy and poor drug targeting are the main cause of early therapy failure. Nanoparticle-based targeting approaches can selectively deliver drugs to the site of inflammation and reduce the risk of side effects by decreasing systemic availability. Here, we developed a nanoparticulate platform for the delivery of the anti-TNF-α antibody adalimumab (ADA) by covalent crosslinking to the particle surface. ADA binding to nanoparticles improved the stability of ADA against proteolytic degradation in vitro and led to a significantly better therapeutic outcome in a murine colitis model. Moreover, immobilization of ADA reduced systemic exposure, which can lead to enhanced therapeutic safety. Thus, nanoparticle protein decoration constitutes a platform through which epithelial delivery of any biological of interest to the inflamed gut and hence a local treatment can be achieved.